2017
DOI: 10.2134/agronj2017.01.0030
|View full text |Cite
|
Sign up to set email alerts
|

Switchgrass Growth and Effects on Biomass Accumulation, Moisture Content, and Nutrient Removal

Abstract: Temporal patterns of plant growth, composition, and nutrient removal impact development of models for predicting optimal switchgrass (Panicum virgatum L.) harvest times for bioenergy. Original time-course data are needed to construct useful models. Objectives were to characterize seasonal trends in yield, tissue moisture, ash content, leaf area index (LAI), interception of photosynthetically active radiation (PAR), and macronutrient accumulation and losses. Plots were subjected to 12 single harvests

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
31
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 26 publications
(35 reference statements)
11
31
2
Order By: Relevance
“…On average, Alamo switchgrass cultivar under irrigated conditions removed 28.5 to 35.7 g N m −2 , 2.52 to 3.48 g P m −2 , and 29.6 to 38.4 g K m −2 per yr. No significant differences were observed in macronutrients (N, P, and K) uptake among different treatments except for the freshwater‐gypsum combination, which was lower than the other treatments. Macronutrients uptake by switchgrass in our study was higher than that reported for other cultivars of switchgrass grown under rainfed conditions (Ashworth, Rocateli, West, Brye, & Popp, ; Oliveira, West, Afif, & Palencia, ). However, our results were comparable to macronutrient removal under two‐cut harvest system of switchgrass under either rainfed (Kering, Butler, Biermacher, Mosali, & Guretzky, ) or freshwater irrigation (Kimura, Collins, & Fransen, 2015).…”
Section: Resultscontrasting
confidence: 81%
“…On average, Alamo switchgrass cultivar under irrigated conditions removed 28.5 to 35.7 g N m −2 , 2.52 to 3.48 g P m −2 , and 29.6 to 38.4 g K m −2 per yr. No significant differences were observed in macronutrients (N, P, and K) uptake among different treatments except for the freshwater‐gypsum combination, which was lower than the other treatments. Macronutrients uptake by switchgrass in our study was higher than that reported for other cultivars of switchgrass grown under rainfed conditions (Ashworth, Rocateli, West, Brye, & Popp, ; Oliveira, West, Afif, & Palencia, ). However, our results were comparable to macronutrient removal under two‐cut harvest system of switchgrass under either rainfed (Kering, Butler, Biermacher, Mosali, & Guretzky, ) or freshwater irrigation (Kimura, Collins, & Fransen, 2015).…”
Section: Resultscontrasting
confidence: 81%
“…Potassium removal was more than four times greater than P removal, which has been observed by others (Woodson et al, 2013;Ashworth et al, 2017). Switchgrass P and K removal (via biomass harvests) was estimated at 10.2 to 19.9 and 52.4 to 93.5 kg ha -1 yr -1 , respectively, across harvest dates (Table 3).…”
Section: Cultivarsupporting
confidence: 68%
“…1). Similarly, in a time-course biomass yield and composition study in Arkansas, Ashworth et al (2017) observed peak yield later in the season (27 September). This indicates precipitation and killing frost frequency may be a main driver for biomass losses post-growing-season.…”
Section: Yield Variance By Cultivar and Harvest Datementioning
confidence: 75%
“…However, timing is generally optimized to accommodate the competing interests of maximizing biomass yield and recycling nutrients to belowground tissues. Biomass yield is negatively affected by harvest delays, and as much as one-third of switchgrass can be lost between peak harvest and post-senescence (Gorlitsky et al, 2015;Serapiglia et al, 2016a,b;Ashworth et al, 2017). Most studies recommend late fall or winter harvest dates to avoid significant yield losses while achieving high nutrient resoprtion (Gorlitsky et al, 2015;Serapiglia et al, 2016a,b;Ashworth et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Following peak biomass, the plants tend to lose biomass due to three processes: resorption of nutrients to belowground tissues (Yang et al, 2009;Lindsey et al, 2013;Ashworth et al, 2017), weathering of dry and brittle aboveground biomass components (Adler et al, 2006;Anderson et al, 2013), and lodging, resulting in materials that are too low to the ground to harvest effectively (Adler et al, 2006;Anderson et al, 2013). In terms of biomass quality, earlier harvests have typically been reported as more digestible following biological conversion (Bals et al, 2010;Dien et al, 2013), however later harvests tend to have a greater proportion of structural carbohydrates (Adler et al, 2006;Anderson et al, 2013;Lindsey et al, 2013), the substrate for microbial-mediated biofuel production.…”
Section: Introductionmentioning
confidence: 99%